1993
DOI: 10.1002/ajpa.1330900304
|View full text |Cite
|
Sign up to set email alerts
|

Elastic properties of human supraorbital and mandibular bone

Abstract: Elastic constants, including the elastic modulus, the shear modulus, and Poisson's ratio, were measured on human craniofacial bone specimens obtained from the supraorbital region and the buccal surfaces of the mandibles of unembalmed cadavers. Constants were determined using an ultrasonic wave technique in three directions relative to the surface of each sample: 1) normal, 2) tangential, and 3) longitudinal. Statistical analysis of these elastic constants indicated that significant differences in the relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
129
7
2

Year Published

1996
1996
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 151 publications
(152 citation statements)
references
References 46 publications
14
129
7
2
Order By: Relevance
“…This is important considering the role that the cranial vault plays in protection of the brain, and the finding that the cranial vault is denser than some postcranial bones. A comparison of our current findings to previous work on the human mandible in our laboratory (Dechow et al, 1993;Schwartz-Dabney and Dechow, in press) shows that parietal cortical bone is on average less dense than that of the mandible. However, density in the mandible varies by region and density in the parietal bone is greater than in the least-dense regions of the mandible, such as at the symphysis.…”
Section: Table 3 Elastic Moduli In Gpasupporting
confidence: 70%
See 4 more Smart Citations
“…This is important considering the role that the cranial vault plays in protection of the brain, and the finding that the cranial vault is denser than some postcranial bones. A comparison of our current findings to previous work on the human mandible in our laboratory (Dechow et al, 1993;Schwartz-Dabney and Dechow, in press) shows that parietal cortical bone is on average less dense than that of the mandible. However, density in the mandible varies by region and density in the parietal bone is greater than in the least-dense regions of the mandible, such as at the symphysis.…”
Section: Table 3 Elastic Moduli In Gpasupporting
confidence: 70%
“…The results demonstrate that determination of material orientation in cranial vault cortical bone is essential prior to measurement of elastic properties. A previous study in our laboratory (Dechow et al, 1993) showed a significant difference between the elastic properties of cortical bone taken from the superorbit compared to the buccal surface of the inferior border of the mandibular corpus. The mandibular cortical bone is stiffer and denser, and has a consistent anisotropy in the plane of the cortical plate.…”
Section: Materials Propertiesmentioning
confidence: 72%
See 3 more Smart Citations